Amidst experiments, controversies and invisibilities: the constitution of organ transplantation as a therapeutic practice - Jasper, Vitor (Ilha Revista de Antropologia, 2021)
This article aims to understand the process of constitution of organ transplantation as a therapeutic practice. Based in the field of Anthropology of Science and Technology, we highlight some elements that have been fundamental for the development of this process, namely: the technique that allows the surgical connection of blood vessels; the pharmacological resources that help in the treatment of rejection of the transplanted organ; and the debates on the definition of brain death. These elements together resulted in the construction of this "breakthrough" and helped validate this technique. Revisiting this process enables us to understand how a discipline that is intended to be universal and objective, such as medicine, builds “truths”. Finally, we defend that these elements continue to have agency over transplantation and produce effects on people’s lives.